The uses of messaging apps and social media groups in the daily life of platform delivery workers: how to play the rules of the game and the production of collective identities - André Scerb (Geografares, 2022)
This article, a partial result of a master’s research in progress, addresses the dynamics and interactions established among platform delivery workers through groups in instant messaging applications and social media. First, it presents the mismatch between the representations made by the platform companies about workers and the ways in which they see themselves and understand their work. Then, the article discusses the uses of instant messaging applications, paying attention to the main patterns of worker’s interaction on digital environments in order to show that there are ambiguous rationalities that guide their formulations about the work. In addition, that these spaces have a decisive role in the creation of collective identities based on the appreciation of work and the sacrifice linked to it. The methodology used was based, on one hand, on the analysis of materials extracted from social media pages and institutional websites of the companies Rappi and iFood in Brazil. On the other hand, it was conducted an empirical digital research, of ethnographic inspiration, in groups of delivery workers on WhatsApp, Telegram and pages of these workers on Facebook.
Keywords: labor markets; Entrepreneurial solidarities; collective identities; plataform work